Kelahiran Anak Sapi Hasil Fertilisasi secara in Vitro dengan Sperma - E M Kaiin; S Said; B Tappa (Faculty of Animal Science, Bogor Agricultural University, 2008)
The aim of this study was to know the viability of embryo after fertilized in vitro with frozen separated sperm (sexing sperm). Eleven frozen embryos were transferred to six Bali cow and five FH cow recipients. Two Bali cow recipients were positively pregnant but only one born as male calf which was appropriate with sex of straw being inseminated (Y sperm). One FH cow recipient was also pregnant but aborted in 2.5 months of pregnancy. It was concluded that embryo resulted from in vitro fertilization (IVF) with sexing sperm could grow and develop to be a calf which was appropriate with the sex of straw inseminated. Key words: sperm sexing, IVF, embryo transfer, Bali cow